High-voltage switchgear and controlgear. Cable connections for gas-insulated metal-enclosed switchgear for rated voltages above 52 kV - Fluid-filled and extruded insulation cables - Fluid-filled and dry-type cable terminations Part 209, (21st September 2022) - British Standards Institution,
No abstract available